PEMBUATAN MOU SEBAGAI STRATEGI PERLUASAN JARINGAN PENJUALAN PAKET WISATA DI BIRO PERJALANAN PRASADAM TOUR KLATEN - , NANANG FARIYANTO, Ghifari Yuristiadhi, S.S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Within a few years tourism industry plays an important role in increasing state foreign exchange revenue, especially oil and gas energy at outside area. In economic crisis which was happening at Indonesia on 21st century, Indonesia Tourism Industry still growth, even it shows significant enhancement. In a rhetorical, growth tourism industry especially in Indonesia travel agent involved which recently try to sell its tour package. Based on that reason, The Writer wants to know, how the marketing strategy can be apply in network expansion to sell the tour package. The other purpose of the writing is how to choose market segmentation, binds the consumer in the regulation of travel agents in the legalization and non-formal, and the role of travel agents to be partners potential tourists. The marketing strategy which applied of sales of tour package in the travel agent is one of important part for company rotation. As a travel agent, it has more variations in handling of tourist. When bidding until the transaction in purpose, price, facility, and feedback, providing information major tourist destination in the tourist destination make package tour looked attractive, even it can provide a maximum service for tourist and it will be the main key of circulation in the performance of travel agent for determination of right the use marketing methods, because it can recognize the tourists personally.